The Pursuit of Existential Meaning and Social Justice in Naguib Mahfouzâ€™s Three Short Stories: â€œZaabalawiâ€, â€œA Day for Saying Goodbyeâ€, and â€œThe Answer is Noâ€ - Sutanto, Dian Natalia; Mendorofa, Melania Prischa; Apriyanti, Teti (Indonesian Journal of English Language Studies (IJELS), 2017)
Mahfouzâ€™s literary fame is mainly based on his novels which become the main source for the critics to understand his whole literary visions. Mahfouzâ€™s short stories, on the other hand, are considered secondarily valuable by the critics as the remainder of the ideas from his novels. This paper proposes that Mahfouzâ€™s short stories are as important as his novels in a sense that they highlights or magnify particular aspects of Mahfouzâ€™s visions. From the analysis of three Mahfouzâ€™s short stories entitled â€œZaabalawiâ€, â€œA Day for Saying Goodbyeâ€, and â€œThe Answer is Noâ€, some of his essential themes and literary visions, which developed further in his novel, are identified. In Zaabalawi, the persistence in maintaining hope of finding meaningful life in spite of the persisting tragedy in human life is emphasized by Mahfouz. In A Day for Saying Goodbye, Mahfouz depicts the futility of modernity without adherence to religious values. In The Answer is No, by depicting the shift of gender relations and accomodating the marginalized womenâ€™s resistence to patriarchy, Mahfouz encourages the reformation of unjust societal structure. Â Keywords: womenâ€™s resistance, existential meaning, social justice